Aspirin desensitization for aspirin‐exacerbated respiratory disease (Samter's Triad): a systematic review of the literature. Issue 11 (16th July 2013) - Xu, Jason J.; Sowerby, Leigh; Rotenberg, Brian W.
<x xml:space="preserve">Abstract</x> Objectives To critically review the current literature regarding aspirin desensitization treatment for nasal polyposis in patients with Aspirin‐Exacerbated Respiratory Disease (AERD). Study Design Systematic review of the literature. Methods All English literature published between January 1995 and February 2013 reporting specifically nasal outcomes following aspirin desensitization in AERD patients were eligible for inclusion. Exclusion criteria were non‐investigative, non‐human, and ex‐vivo studies. Studies were categorized by level of evidence and evaluated for quality using the Downs and Black scale. Results A total of 614 citations were retrieved and eleven studies met the criteria for analysis. Outcome measurements included self‐reported symptom scores, amount of corticosteroid use, rate of revision surgery, and quantitative measurements such as rhinomanometry. Overall, most studies reported a significant improvement in symptom scores, decrease in corticosteroid use, and decrease in revision surgery. A few studies showed promising results with quantitative outcomes. However, most studies were of Level 2 evidence with small samples sizes. Rates of adverse events ranged from 12.5% to 23%. Conclusions Unlike traditional treatments for nasal polyposis, aspirin desensitization targets AERD etiology rather than phenotype and can be an effective therapeutic option. While the current literature shows encouraging results, additional studies are needed to better define clinical benefits.